Initiation and Growth in Novel Ignition Threshold Experiments (IGNITE) - Heal, Kieran (Cranfield University, 2022)
It is well known that the sensitivity of energetic materials increases with damage. However, the sensitivity and damage characteristics of polymer bonded explosives (PBX) have, to date, largely been studied separately. As such, the physical mechanisms through which damage influences sensitivity are poorly understood. The project presented seeks to bring together the fields of damage and sensitivity in PBXs. It will do this by firstly exploiting controllable methodologies for imparting damage across a range of strain rates, as well as exploring the use of the time-temperature superposition principle as a substitute for strain rates which are practically challenging to achieve. The sensitivity of damaged PBXs will then be studied in both thin and thick shock regimes to produce ignition criterion curves, referred to as James Curves. Throughout this work, imaging of the material microstructure will be undertaken to investigate the underlying mechanisms affecting the results.Overall, this these will provide the first complete experimental picture of damage to PBXs across the high and low strain rate regimes and its influence on the initiation of those materials. This picture is an important part of understanding how the safety and reliability of PBXs can be ensured into the future.
Keywords: PBX; Sensitivity; Damage; DSDS2022; DSDS2022 3MT